2014
DOI: 10.1186/1465-9921-15-65
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine improves established monocrotaline-induced pulmonary hypertension in rats

Abstract: BackgroundThe outcome of patients suffering from pulmonary arterial hypertension (PAH) are predominantly determined by the response of the right ventricle to the increase afterload secondary to high vascular pulmonary resistance. However, little is known about the effects of the current available or experimental PAH treatments on the heart. Recently, inflammation has been implicated in the pathophysiology of PAH. N-acetylcysteine (NAC), a well-known safe anti-oxidant drug, has immuno-modulatory and cardioprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 48 publications
0
28
1
Order By: Relevance
“…injections to induce PAH, or the same volume of the vehicle, as previously described (2). The PCPA-effected groups of rats received PCPA (i.p.…”
Section: Methodsmentioning
confidence: 99%
“…injections to induce PAH, or the same volume of the vehicle, as previously described (2). The PCPA-effected groups of rats received PCPA (i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Hemodynamic measurements were recorded as previously described. 8 For the Fulton index of right ventricular (RV) hypertrophy, the ratio of RV weight to left ventricular plus septum weight was calculated.…”
Section: Hemodynamic Measurements Evaluation Of Right Ventricular Hymentioning
confidence: 99%
“…These inflammatory cytokines were able to stimulate an increased in the expression and activity of Nox1 (22). NAC produces its MCT-PH protective effects through anti-inflammatory and immunomodulatory mechanisms (9)(10)(11). The present study compared pulmonary arterial pressure and PVR in the MCT and NAC groups, and further validated the conclusion that NAC acts via anti-inflammatory and immunomodulatory mechanisms; in addition, it was demonstrated from one lateral side that, different from hypoxia-induced PH, MCT-PASMCs exhibited Nox1-mediated regulation of cell proliferation rather than Nox4, and this was caused by different upstream stimulatory factors mediating different signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…N-acetylcysteine (NAC) is a synthetic precursor of GSH, which exhibits antioxidant properties and has been clinically applied for the treatment of idiopathic pulmonary fibrosis and ischemia reperfusion injury (8)(9)(10). A previous study demonstrated that NAC was able to improve PH and right ventricular function via immune regulatory mechanisms (11). Therefore, it was hypothesized that NAC may protect against oxidation, thereby alleviating MCT-induced pulmonary vascular and right heart diseases.…”
Section: Introductionmentioning
confidence: 99%